The Importance of the dentist in the Intensive Care Unit - Candido, Evelin Emanuelle (2022)
The incorporation of the dentist in the multidisciplinary team is fundamental for improving the quality of life of patients hospitalized in ICU beds, thus avoiding possible infections that may compromise the patient systemically. Good oral health of patients hospitalized in the intensive care unit is essential for a good prognosis, and the dentist specialized in hospital dentistry is responsible for this care of the bedridden patient, guiding his team on the correct protocol to be performed. The purpose of this study was to conduct a literature review on the importance of the dentist in the ICU, and its integration into the Material team and methods; Searches were conducted in bibliographic databases, such as Google Scholar, Scielo and Pubmed. Multidisciplinary. Twenty-four articles were selected that confirm the importance of the presence of the dentist in the hospital environment, thus providing the patient with a decrease in cases of infection, such as nosocomial pneumonia, pneumonia associated with mechanical ventilation, among others. The dentist included in the multidisciplinary team provides the patient with a care in which the patient is seen as a whole and not in parts, reducing the time of hospitalization and risk of systemic complications through oral health care.